Inside Back Cover: Programmed Photodegradation of Polymeric/Oligomeric Materials Derived from Renewable Bioresources (Angew. Chem. Int. Ed. 4/2015). Issue 4 (29th December 2014) - Rajendran, Saravanakumar; Raghunathan, Ramya; Hevus, Ivan; Krishnan, Retheesh; Ugrinov, Angel; Sibi, Mukund P.; Webster, Dean C.; Sivaguru, Jayaraman
<x xml:space="preserve">Abstract</x> A cradle‐to‐cradle approach for the synthesis of biomass‐derived polymers and their degradation back to the monomeric units is presented. In their Communication on page 1159 ff., M. P. Sibi, D. C. Webster, J. Sivaguru, et al. that the recovered monomers can be reused to synthesize the polymers and oligomers. The polymers and oligomers synthesized from biomass‐derived monomers which also incorporate a phototrigger can be degraded back to the monomers under irradiation of UV light.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>